Sulfated bromophenols from Osmundaria obtusiloba (C. Agardh) R. E. Norris (Rhodophyta, Ceramiales) - Carvalho,Luciana Retz de (2006)
Two new sulfated oligobromophenols from the marine red algae Osmundaria obtusiloba, 4-(1'-potassium sulfate, 2,3-dibromo, 1',4,5-trihydroxybenzyl) - 4''-(1'''-potassium sulfate, 2'',3''-dibromo, 1''',4'',5''-trihydroxybenzyl) sulfate and 1'-(2, 3-dibromo, 4-potassium sulfate, 1', 4, 5-trihydroxybenzyl) - 4''-(1''' potassium sulfate, 2'', 3''-dibromo, 1''', 4'', 5'' trihydroxybenzyl) sulfate, are herein reported. Besides them it was obtained 2, 2', 3, 3'-tetrabromo-4, 4', 5, 5'-tetrahydroxydiphenylmethane, 2, 3-dibromo-p-hydroxybenzyl methyl ether (methyl lanosol), dipotassium 2,3-dibromo-5-hydroxybenzyl 1',4-disulfate, 24-methylenecolest-5-en-3-beta-ol and alpha-D-mannopyranosyl-(1->2')-glycerate (digeneaside). The structures were determined by analysis of the spectroscopic data (IR, NMR and MS) and comparison with the literature. The 13CNMR data for dipotassium 2,3-dibromo-5hydroxybenzyl-1',4-disulfate are described here for the first time. The present study also suggests a mild method to isolate and to purify sulfated compounds.